Analisis Cash Ratio, Debt to Equity Ratio, and Sales Growth on Company Value for Food and Beverage Companies During the 2015-2021 Period - Siti Zuliyana; Subur Karyatun; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
The purpose of this study is to analyze the Cash Ratio, Debt to Equity Ratio, & Sales Growth on company value for food and beverage companies during the 2015-2021 period. The population in this study are companies in the food and beverage sector which are listed on the Indonesia Stock Exchange between 2015- 2021. Sampling was done by purposive sampling from 20 companies. Documentation is used as a method of data collection. Study data were analyzed using a panel data regression approach with a significance level of 0.05 using STATA 16 software. This analysis shows that Debt to Equity and sales growth variables have a positive and significant effect on cash ratios which have no effect on firm value.